Pengaruh Inflasi, Tingkat Suku Bunga, Nilai Tukar, PDB, Bagi Hasil Terhadap Deposito Mudharabah Bank Syariah Bukopin - Anniesatun Nurul Aliefah (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2021)
The purpose of this study was to determine the effect of inflation, bank interest rates, exchange rates, GDP and profit sharing rates on the amount of Mudharabah deposits of Bank Syariah Bukopin. The data used in this research is quarterly data for 2008-2015 taken from various sources. This study uses quantitative methods with secondary data and is assisted by the SPSS 20 program. The results of this study indicate that inflation has no effect on mudharabah deposits as indicated by the sig. > α, namely 0.725 > 0.05 and t count -357. The interest rate variable has a negative effect on mudharabah deposits as indicated by the sig. 0.008 < 0.05 and t count -2.943. The profit sharing variable has a significant effect on mudharabah deposits with a sig value. 0.001 <0.05 and the calculated t value is 3.708. The exchange rate variable has no effect on mudharabah deposits with a sig > α value, namely 0.71 > 0.05 and a t count 1.910. The GDP variable has no effect on mudharabah deposits with a sig > α value, namely 0.71 > 0.05 and a t-count value of 1. 906. The R2 value is 0.770 which means that the independent variables in this regression model are able to explain 77.0% of the dependent variable and the remaining variables are explained others that are not included in this model.